Encuesta sobre el Derecho de excepción - Manuel Aragón Reyes; Raúl Canosa Usera; Ana Carmona Contreras; Pedro Cruz Villalón; Carlos Garrido López; Miguel Ángel Presno Linera; Tomas de la Quadra-Salcedo y Fernández del Castillo, (Teoría y Realidad Constitucional, 2022)
Encuesta sobre el Derecho de excepción